2018
DOI: 10.1371/journal.pone.0202955
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the central hypothalamic-pituitary-adrenal axis in hair growth and melanogenesis among different mouse strains

Abstract: Stress has been demonstrated to play an important role in hair follicle function and the pathogenesis of some hair disorders. The central hypothalamic-pituitary-adrenal (HPA) axis is activated by stress stimuli, synthesizes and releases various components and eventually induces the pathogenesis and recurrence of peripheral diseases. Our aim is to compare the different responses under exposure of stress in hair follicle function among different mouse strains, and to detect the involvement of the central HPA axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…[ 71 ] However, recent data from mice have provided the first functional evidence for its involvement in HF growth and melanogenesis. [ 80 ] Again, GWAS findings provide evidence that this endocrine signalling pathway is involved in AGA. The lead variant at 17q21.31 (rs117365970, P = 3.2 × 10 −177 , β = −0.10, SE = 0.004) is located within the fourth intron of the gene that encodes the G protein‐coupled receptor CRHR1 (corticotropin‐releasing hormone receptor 1), which binds neuropeptides of the CRH family.…”
Section: Corticotropin‐ and Gonadotropin‐releasing Hormone Signallingmentioning
confidence: 99%
“…[ 71 ] However, recent data from mice have provided the first functional evidence for its involvement in HF growth and melanogenesis. [ 80 ] Again, GWAS findings provide evidence that this endocrine signalling pathway is involved in AGA. The lead variant at 17q21.31 (rs117365970, P = 3.2 × 10 −177 , β = −0.10, SE = 0.004) is located within the fourth intron of the gene that encodes the G protein‐coupled receptor CRHR1 (corticotropin‐releasing hormone receptor 1), which binds neuropeptides of the CRH family.…”
Section: Corticotropin‐ and Gonadotropin‐releasing Hormone Signallingmentioning
confidence: 99%
“…The function of those neurotransmitters in the physiological and pathological state of the skin remains poorly understood. Moreover, 5-HT is a phylogenetically ancient signaling molecule and neurotransmitter, which actions are mediated through 5-HT receptors [ 26 , 27 ]. It has been reported that 5-HT receptors are widely detected on mammalian dermal fibroblasts and melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The open-field test (OFT), forced swimming test (FST), and tail suspension test (TST) were carried out as previously described [ 31 , 49 ]. The OFT was used to observe the behavioral changes in each group of mice and to test the spontaneous activity of the mice.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence analysis was conducted as described previously [29,31]. The slides of skin were stained with primary antibodies against CD8 (Abcam, Cambridge, UK, ab217344) and left overnight at 4 • C. After incubation with the secondary antibody, cell nuclei were counterstained with DAPI (Solarbio, Beijing, China).…”
Section: Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation